Rehabilitation of memory following brain injury (ReMemBrIn): study protocol for a randomised controlled trial - das Nair, Roshan; Lincoln, Nadina; Ftizsimmons, Deborah; Brain, Nicola; Montgomery, Alan; Bradshaw, Lucy; Drummond, Avril E.R.; Sackley, Catherine Mary; Newby, Gavin; Thornton, Jim; Stapleton, Sandip; Pink, Anthony (BioMed Central, 2015)
Background Impairments of memory are commonly reported by people with traumatic brain injuries (TBI). Such deficits are persistent, debilitating, and can severely impact quality of life. Currently, many do not routinely receive follow-up appointments for residual memory problems following discharge.